CircEpc1 Promotes Ricin Toxin-Induced Inflammation via Activation of NF-κB and MAPK Signaling Pathways by Sponging miR-5114 - Dong, Mingxin; Zhang, Xiaohao; Yu, Haotian; Wang, Yan; Chang, Ying; Sun, Chengbiao; Zhang, Jianxu; Zhao, Na; Yu, Kaikai; Sun, Guangchao; Zhao, Guiru; Xu, Na; et al. (Frontiers in Pharmacology, 2021)
Increasing studies have concentrated on investigating circular RNAs (circRNAs) as pivotal regulators in the progression of numerous diseases and biological processes and abundant evidence shows that circRNAs are participated in the regulation of innate immune responses. Several studies showed that Ricin Toxin (RT) could induce inflammatory injury. There was no research on the particular functions and underlying mechanisms of circRNAs in RT-induced inflammation. In this study, RNA sequencing performed on RT-treated and normal RAW264.7 macrophage cells was used to investigated the differentially expressed circRNAs. Based on the dataset, the expression of circEpc1 (mmu_circ_0000842) was identified higher in RT-treated cells. Moreover, gain-and-loss function assays showed that circEpc1 function as a promoter in RT-induced inflammation in vivo and in vitro. Mechanistically, circEpc1 acted as a miR-5114 sponge to relieve the suppressive effect of miR-5114 on its target NOD2 and thereby activating NF-κB and MAPK signaling pathways. Our results illuminated a link between RT-induced inflammation and the circEpc1 regulatory loop and provided novel insight into the functions of circRNA in innate immune, which may emerge as a potential target in immunotherapy to control the RT-induced inflammatory injury.